Integrating pedagogical content knowledge and pedagogical/psychological knowledge in mathematics - Harr, Nora; Eichler, Andreas; Renkl, Alexander (Frontiers in Psychology, 2014)
In teacher education at universities, general pedagogical and psychological principles are often treated separately from subject matter knowledge and therefore run the risk of not being applied in the teaching subject. In an experimental study (N = 60 mathematics student teachers) we investigated the effects of providing aspects of general pedagogical/psychological knowledge and pedagogical content knowledge in an integrated or separated way. In both conditions (‘integrated’ vs. ‘separate’), participants individually worked on computer-based learning environments addressing the same topic: use and handling of multiple external representations, a central issue in mathematics. We experimentally varied whether pedagogical/psychological knowledge aspects and pedagogical content knowledge aspects were treated integrated or apart from one another. As expected, the integrated condition led to greater application of pedagogical/psychological aspects and an increase in applying both knowledge types simultaneously compared to the separated condition. Overall, our findings indicate beneficial effects of an integrated design in teacher education.